1999
DOI: 10.1073/pnas.96.8.4633
|View full text |Cite
|
Sign up to set email alerts
|

Evectins: Vesicular proteins that carry a pleckstrin homology domain and localize to post-Golgi membranes

Abstract: We have identified two vesicular proteins, designated evectin (evt)-1 and -2. These proteins are Ϸ Ϸ25 kDa in molecular mass, lack a cleaved N-terminal signal sequence, and appear to be inserted into membranes through a Cterminal hydrophobic anchor. They also carry a pleckstrin homology domain at their N termini, which potentially couples them to signal transduction pathways that result in the production of lipid second messengers. evt-1 is specific to the nervous system, where it is expressed in photoreceptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 32 publications
(35 reference statements)
0
39
1
Order By: Relevance
“…AAC39675), interacted with several phosphoinositides (Figure 2). The PH domain of a protein of unknown function, termed evectin-2, which localizes to post-Golgi membranes [25], showed a moderate affinity for PtdIns(3,4,5)P $ , but also interacted more weakly with several other phosphoinositides (Figure 2). None of the PH domains for which lipid-binding properties were investigated (as shown in Figure 2) interacted with phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine or phosphatidylinositol in the protein-lipid overlay assay (results not shown).…”
Section: Table 2 Relative Affinities Of Pepp1 Fapp1 Wild-type and Mumentioning
confidence: 99%
“…AAC39675), interacted with several phosphoinositides (Figure 2). The PH domain of a protein of unknown function, termed evectin-2, which localizes to post-Golgi membranes [25], showed a moderate affinity for PtdIns(3,4,5)P $ , but also interacted more weakly with several other phosphoinositides (Figure 2). None of the PH domains for which lipid-binding properties were investigated (as shown in Figure 2) interacted with phosphatidylcholine, phosphatidylethanolamine, phosphatidylserine or phosphatidylinositol in the protein-lipid overlay assay (results not shown).…”
Section: Table 2 Relative Affinities Of Pepp1 Fapp1 Wild-type and Mumentioning
confidence: 99%
“…Two other proteins with PH domains play potentially important roles in the retina. Evictin-1 can localize to rhodopsin-laden, postGolgi membranes in photoreceptor cells, suggesting that the protein may be involved in postGolgi traffi cking of membranes ( 202 ). PHR1 is present in outer segments and binds to transducin ␤ ␥ subunits but does not bind to inositol phosphates; however, PI lipids were not tested ( 204 ).…”
Section: Phosphoinositides In Retina Structure and Functionmentioning
confidence: 99%
“…The best examples are Akt isoforms ( 52,135 ), IRS-1, IRS-2 ( 52, 68, 69 ), Grb14 ( 157 ), Evictin-1 ( 202 ), PHR1 ( p leckstrin h omology domain r etinal protein) ( 203,204 ), and recently identifi ed Akt dephosphorylating enzymes PHLPP (PH domain and leucine rich repeat protein phosphatases) and PHLPPL (PH domain and leucine rich repeat protein phosphatase-like) ( 205 ). Deletion of two PI-binding proteins, Akt2 ( 135 ) and IRS-2 ( 69 ), in the retina results in photoreceptor degeneration.…”
Section: Phosphoinositides In Cellular Regulationmentioning
confidence: 99%
“…Immunohistochemistry and chemical extraction studies on the photoreceptor outer segment have shown that PHR1 is an integral membrane protein (Xu et al, 1999). PHR1 contains an N-terminal pleckstrin homology domain (Krappa et al, 1999;Xu et al, 1999). Pleckstrin homology (PH) domains are 100-to 120-amino acid modules best known for their ability to bind to phosphoinositides (Lemmon et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 71 clones by histidine nutritional selection and β-galactosidase (β-gal) activity. The inserts from the isolated clones were sequenced, leading to the identification of four overlapping clones that encode the C-terminal region of a protein named PHR1 (Krappa et al, 1999;Xu et al, 1999) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%